Quality of life in women with urinary incontinence seeking care using e-health - Ylva Åström; Ina Asklund; Anna Lindam; Malin Sjöström (BMC, 2021)
Abstract Background Quality of life (QoL) in women with urinary incontinence (UI) is mainly affected by UI severity, but it is also affected by the UI subtype, comorbidities, age, and socioeconomic status. e-Health is a new method for providing UI treatment. This study aimed to identify factors with the highest impact on QoL in women that turned to e-health for UI self-management. Methods We analysed data from three randomized controlled trials (RCTs) that evaluated e-health treatments for UI. We included baseline data for 373 women with stress urinary incontinence (SUI) and 123 women with urgency/mixed UI (UUI/MUI). All participants were recruited online, with no face-to-face contact. Participants completed two questionnaires: the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF, range: 0-21 points), for assessing UI severity, and the ICIQ Lower Urinary Tract Symptoms Quality of Life (ICIQ-LUTSqol, range: 19-76 points), for assessing condition-specific quality of life (QoL). To identify factors that impacted QoL, we constructed a linear regression model. Results The mean ICIQ-LUTSqol score was 34.9 (SD 7.6). UI severity significantly affected QoL; the adjusted mean ICIQ-LUTSqol score increased by 1.5 points for each 1.0-point increase in the overall ICIQ-UI SF score (p < 0.001). The UI type also significantly affected QoL; the adjusted mean ICIQ-LUTSqol score was 2.5 points higher in women with UUI/MUI compared to those with SUI (p < 0.001). Conclusions We found that women that turned to e-health for UI self-management advice had a reduced QoL, as shown previously among women seeking UI care through conventional avenues, and that the severity of leakage had a greater impact on QoL than the type of UI. Condition-specific factors impacted the QoL slightly less among women that turned to e-health, compared to women that sought help in ordinary care. Thus, e-health might have reached a new group of women in need of UI treatment.